Swedish electorate 1887-1968 - Lewin, Leif (Uppsala University, 2013)
The study concerns the parliamentary elections (for the second chamber) from 1887, the first election of modern type in Sweden´s history with clearly demarcated political groupings within the electorate, to 1968, the last election under the bicameral parliamentary system.
The aim is to study the mobilization of the Swedish electorate during the period and how social structure influences political behaviour. The data are of two types: political data and social data.

Purpose:

Study the mobilization of the Swedish electorate during 1887 to 1968.

Studien omfattar riksdagsval (till den andra kammaren) från 1887, det första valet av modern typ i Sveriges historia med klart avgränsade politiska grupperingar inom väljarkåren, till 1968, det sista valet med tvåkammarsystem.
Syftet är att studera förändringen av det svenska valdeltagande under den här tidsperioden, samt att se hur sociala strukturer påverkar det politiska beteendet. Datamaterialet består av två olika typer, politiska data och sociala data.

Syfte:

Studera mobiliseringen av den svenska väljarkåren under åren 1887 till 1968.
Svenska väljarkåren 1887-1968
Keywords: elections; val; occupations; yrken; politics; politik; social class; social klass; election data; valdata; party politics; partipolitik; political history; politisk historia; Employment; Sysselsättning; POLITICS; POLITIK; Elections; Val; Social conditions and indicators; Sociala förhållanden och indikatorer; HISTORY; HISTORIA; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; History; Historia